2014
DOI: 10.1093/pubmed/fdu092
|View full text |Cite
|
Sign up to set email alerts
|

Method of invitation and geographical proximity as predictors of NHS Health Check uptake

Abstract: BackgroundUptake of NHS Health Checks remains below the national target. Better understanding of predictors of uptake can inform targeting and delivery. We explored invitation method and geographical proximity as predictors of uptake in deprived urban communities.MethodsThis observational cohort study used data from all 4855 individuals invited for an NHS Health Check (September 2010–February 2014) at five general practices in Stoke-on-Trent, UK. Attendance/non-attendance was the binary outcome variable. Predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 13 publications
(18 reference statements)
2
34
0
Order By: Relevance
“…Although not the primary aim of the study, it was possible to observe variation in attendance according to sex, age and ethnicity. As with other studies of NHS HC uptake, the likelihood of attendance increased in female patients [23,[39][40][41][42] and with increasing age [23,39,40,42]. Our findings that those with black ethnicity were more likely to attend and that those whose ethnicity is not recorded were less likely to attend are in accordance with the results of other studies [5,43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although not the primary aim of the study, it was possible to observe variation in attendance according to sex, age and ethnicity. As with other studies of NHS HC uptake, the likelihood of attendance increased in female patients [23,[39][40][41][42] and with increasing age [23,39,40,42]. Our findings that those with black ethnicity were more likely to attend and that those whose ethnicity is not recorded were less likely to attend are in accordance with the results of other studies [5,43].…”
Section: Discussionsupporting
confidence: 92%
“…The uptake rate even in the best condition of this study remained lower than average (48.5%) suggesting other techniques should be used alongside letters and SMS. One study using observational cohort methodology showed that if a patient is invited by phone or approached verbally in-practice, compared to a letter alone or in addition to a letter, they are three times more likely to attend an NHS HC [39]. Similarly, amongst 30 GP practices in Luton, England highest uptake was found for verbal face-to-face NHS HC offers (71.9%), followed by telephone invitation (43%) and finally by letter invitation (29.5%) [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of health checks, an observational study found significantly higher uptake at practices using telephone or verbal health check invitations, either singly or in combination with letters. 34 Telephone or face-to-face invitations to promote health check uptake may be difficult to implement on a large scale, as would be required for the national Health Check programme.…”
mentioning
confidence: 99%
“…A comparison of NHS Health Check coverage (2011)(2012) against expected (APHO) cardiovascular health need found that coverage was significantly higher in PCTs in the most deprived areas compared with the least deprived (Artac et al 2013). Some studies (Donyai & Van den Berg 2009, Labeit et al 2013) agree that people from less advantaged communities are more likely to access CHD risk screening programmes, while others disagree (Horgan et al 2010, Gidlow et al 2015, Chang et al 2015, Cook et al 2016. With respect to age, youth also appears to be a factor lowering rates of presentation and uptake of health checks (Adamson et al 2008, Dalton et al 2011, Cook et al 2016, Robson et al 2016.…”
Section: Variations Across the Care Pathwaymentioning
confidence: 99%